Genotypes and drug resistance pattern of Mycobacterium tuberculosis complex among clinically diagnosed pulmonary tuberculosis patients - Alemayehu, Alem; Wassie, Liya; Alemayehu, Dawit Hailu; Adnew, Bethlehem; Neway, Sebsib; Tefera, Dessalegn Abeje; Ayalew, Sosina; Hailu, Elena; Ayele, Samuel; Seyoum, Berhanu; Bobosha, Kidist; Abebe, Markos; et al. (Frontiers in Public Health, 2024)
BackgroundClinically diagnosed pulmonary tuberculosis (TB) (CDPTB) patients account for a huge proportion of TB. However, little is known about the genetic diversity and drug resistance profile of Mycobacterium tuberculosis Complex (MTBC) strains in this group of patients.MethodUnmatched case–control study was conducted among 313 PTB patients to compare the genetic diversity of MTBC and their drug resistance profiles among CDPTB (n = 173) and bacteriologically confirmed pulmonary TB (BCPTB) (n = 140) patients. Lowenstein-Jensen (LJ) culture, geneXpert and acid fast staining were performed on sputum specimen collected from both CDPTB and BCPTB patients. Spoligotyping, whole genome sequencing (WGS) and phenotypic drug resistance testing (DST) were done for a subset of LJ grown MTBC isolates. Data was analyzed by STATA version 17 software and a p-value <0.05 were considered statistically significant.ResultsThe proportion of lineage 3 was larger among CDPTB patients (31%, 13/42) compared to BCPTB patients (15%, 11/74) (p-value <0.05). A higher proportion of MTBC isolates from CDPTB 16.6% (3/18) were phenotypically resistant to one or more anti-TB drugs than BCPTB 12% (4/33) (p-value >0.05). A single lineage 3 strain resistant to all the primary anti-TB drugs was detected in one CDPTB by both DST methods.ConclusionThe observed differences in the genotypes of MTBC isolates between CDPTB and BCPTB patients may be attributed to challenges in the identification of CDPTB that requires further investigation on sequenced genome of the MTBC strains for better understanding and recommendation based on the current finding. There was also primary drug resistant TB among culture positive CDPTB patients which would be otherwise missed by current national protocols.